U.S. Law and Animal Experimentation: A Critical Primer - Latham, Stephen R. (The Hastings Center report, 2012)
Every country's law permits medical experimentation on animals. While some countries protect particular kinds of animals from being subject to experimentation—notably great apes and endangered species—very few place concrete limitations on what researchers may cause animals to suffer, given sufficient scientific justification. What laws do, instead, is establish standards for the humane treatment and housing of animals in labs, and they encourage researchers to limit or seek alternatives to the use of animals, when doing that is consistent with the scientific goals of their research. The system that has evolved in the United States combines elements of sometimes competing regulatory philosophies. The result is a complex, multilayered system that addresses the most important concerns, but, partly because of historical accident, also leaves some gaps. Even proponents of medical research on animals can see obvious ways in which the regulatory structure could be changed to benefit animals. Perhaps more important, though, is the fact that the existing regulatory structure, imperfect though it may be, is elastic enough to accommodate substantial changes that could reduce unnecessary animal suffering.